A study on the constitutive equation of HC420LA steel subjected to high strain rates. Issue 6 (23rd January 2019) - Cui, Junjia; Wang, Qiong; Dong, Dongying; Jiang, Hao; Zhang, Xu; Li, Guangyao
Abstract: Abstract : In this paper, the influence of strain rate on the mechanical behavior of high-strength low-alloy (HC420LA) steel were studied. Quasi-static and dynamic tensile experiments were performed with strain rates ranging from 0.001 to 500 s −1 at room temperature. The digital image correlation technique was used to obtain the full-field strain. The experimental results showed that HC420LA steel exhibited positive strain rate sensitivity. Based on experimental results, the modified Johnson–Cook (J–C) model was used to model the constitutive behavior of HC420LA steel. Predictions of the standard and modified J–C models were compared using standard statistical parameters. The modified J–C model showed better agreement with the experimental data. Then, numerical simulation of the representative tensile test at a strain rate of 100 s −1 was performed using the finite element code LS-DYNA. Good correlation between the experimental and numerical simulation results was achieved.